2007
DOI: 10.1104/pp.107.099325
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Leaf Development infuguMutants of Arabidopsis Reveals Three Compensation Modes That Modulate Cell Expansion in Determinate Organs

Abstract: In multicellular organisms, the coordination of cell proliferation and expansion is fundamental for proper organogenesis, yet the molecular mechanisms involved in this coordination are largely unexplored. In plant leaves, the existence of this coordination is suggested by compensation, in which a decrease in cell number triggers an increase in mature cell size. To elucidate the mechanisms of compensation, we isolated five new Arabidopsis (Arabidopsis thaliana) mutants (fugu1-fugu5) that exhibit compensation. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
254
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 173 publications
(270 citation statements)
references
References 60 publications
13
254
0
3
Order By: Relevance
“…4B, left). Previously, Ferjani et al (2007) also observed that an3-4, another mutant allele of GIF1, exhibited early cessation of the cell proliferation phase in the leaf-length axis. Moreover, leaves of gif1/2 double and gif1/2/3 triple mutants had only about half the cells of wild-type leaves already at days 6 and 4, respectively (Fig.…”
Section: Kinematic Analysis Of Leaf Area and Cellular Parameters Durimentioning
confidence: 76%
“…4B, left). Previously, Ferjani et al (2007) also observed that an3-4, another mutant allele of GIF1, exhibited early cessation of the cell proliferation phase in the leaf-length axis. Moreover, leaves of gif1/2 double and gif1/2/3 triple mutants had only about half the cells of wild-type leaves already at days 6 and 4, respectively (Fig.…”
Section: Kinematic Analysis Of Leaf Area and Cellular Parameters Durimentioning
confidence: 76%
“…During organ formation, primordium growth is initially driven by cell proliferation, whereas the second growth phase is primarily attributed to postmitotic cell expansion of the differentiating cells through endoreduplication and vacuolization (Donnelly et al, 1999;den Boer and Murray, 2000;Nath et al, 2003). Usually, ploidy levels and cell size are positively correlated, indicating that cell expansion and differentiation depend on the endocycle (Cionini et al, 1983;Melaragno et al, 1993;Gendreau et al, 1998;Joubès et al, 1999;Beemster et al, 2003;Tsukaya, 2006), but ploidy-independent growth mechanisms also exist (De Veylder et al, 2001;Beemster et al, 2002;Jasinski et al, 2002;Schnittger et al, 2003;Ferjani et al, 2007).…”
mentioning
confidence: 99%
“…Such compensatory coordination between cell cycling and expansion is known to occur in the leaves of many mutants and transgenic lines, and has been the topic of several investigations. For example, by considering the manner through which a cell reaches its ultimate size and performing kinematic analyses of cell size dynamism, three classes of compensation have been identified: Class I, an enhanced postmitotic cell expansion rate (seen in angustifolia [an]3-4, fugu2-1/fasciata [fas]1-5, and erecta [er]-102); Class II, an extended post-mitotic cell expansion period (seen in fugu5-1); and Class III, increase in the size of dividing cells (seen in KIP-RELATED PROTEIN 2 [KRP2] over-expressing cells) (Ferjani et al 2007(Ferjani et al , 2008(Ferjani et al , 2010(Ferjani et al , 2013a(Ferjani et al , 2013b(Ferjani et al , 2014. Furthermore, during compensation, cell-autonomous and non-cell-autonomous pathways have been identified (Kawade et al 2010, 2013, Ferjani et al 2013a.…”
Section: Introductionmentioning
confidence: 99%
“…fugu5, a compensation-exhibiting mutant defective in H + -PPase To characterize the mechanisms of compensation, we used screening assays to identify several Arabidopsis mutants, including fugu1 through fugu5, that exhibit typical compensation (Horiguchi et al 2006b, Ferjani et al 2007). Cloning of the causal genes in compensation-exhibiting mutants and dissecting their functions within developing organs has been used to study size regulation in plants.…”
Section: Introductionmentioning
confidence: 99%